A Smart Chatbot for Interactive Management in Beta Thalassemia Patients. (11th May 2022) - Alturaiki, Alma Mohammed; Banjar, Haneen Reda; Barefah, Ahmed Salleh; Alnajjar, Salwa Abdulrahman; Hindawi, Salwa
Abstract : Background . β -thalassemia is an inherited blood disorder that affects the production of hemoglobin molecules owing to the reduction or absence of beta chains. Transfusion therapy has had a key role in extending the lifespan of β -thalassemia patients. This life-saving therapy is linked to numerous assessments and complications that now comprise most thalassemia management considerations. Consequently, many patients do not receive adequate information about the required assessments, as indicated by evidence-based medical guidelines. Patients with β -thalassemia may benefit from chatbots that follow up on their condition and that provide the required assessment information. Self-management will hopefully have a positive impact on health outcomes. Objectives . This study aims to develop a chatbot that can assist in the management of β -thalassemia by providing the assessment information required to monitor patients' statuses. Methods . The chatbot operated as a messaging system. A question/answer system was created based on knowledge pertaining to β -thalassemia assembled from experts, medical guidelines, and articles. Recommendations regarding the patient's follow-up assessment are made based on the answers. Results . A prototype was implemented to demonstrate how the chatbots could dynamically and flexibly provide the assessment information required to follow up on and monitor patients. A small sample of adults with β -thalassemia used the chatbot to examine the system's usability and perceived utility. A system usability scale and utility scale were implemented to complete a post-test survey. The chatbots were considered by 34 patients, of whom the majority (72%) found them easy to use, while more than 90% of patients considered their use beneficial. Most of the participants agreed that the chatbots could improve their knowledge about their β -thalassemia assessments. Conclusion . Our findings suggest that chatbots can be beneficial to the development of recommended tests and management related to the assessment of β -thalassemia.